Special Issue Introduction: Religion and Eco-Resistance Movements in the 21st Century - Witt, Joseph D.; Taylor, Bron (Journal for the Study of Religion, Nature and Culture, 2017)
Joseph D. Witt and Bron Taylor introduce this special issue of Journal for the Study of Religion, Nature and Culture on Religion and Eco-Resistance Movements in the Twenty-First Century.